2017
DOI: 10.1161/hypertensionaha.117.09679
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 2 Receptor and Receptor Mas Are Colocalized and Functionally Interdependent in Obese Zucker Rat Kidney

Abstract: The actions of angiotensin II type 2 receptor (AT2R) and the receptor Mas (MasR) are complex but show similar pro-natriuretic function; particularly AT2R expression and natriuretic function are enhanced in obese/diabetic rat kidney. In light of some reports suggesting a potential positive interaction between these receptors, we tested hypothesis that renal AT2R and MasR physically interact and are inter-dependent to stimulate cell signaling and promote natriuresis in obese rats. We found that infusion of AT2R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 47 publications
5
44
1
2
Order By: Relevance
“…This suggests a functional dependence between AT2 and MasR for the AT2-induced generation of neurospheres. Accumulating evidence shows that both receptors are co-localized, form heterodimers, and have different functional interactions in different cells and experimental conditions [27,[95][96][97], and recent data from our laboratory (unpublished) showed that young AT2-KO mice show a reduced expression of MasR in the substantia nigra and striatum, which may also contribute to the decrease in proliferation and neurogenesis observed in the V-SVZ of AT2-KO mice. Therefore, although RAS receptors have been associated with different cellular and physiological responses, their role in neurogenesis is complex, as shown by the present results that reveal the presence of AT1, AT2, and MasR interactions possibly both in physiological or pathological situations.…”
Section: Discussionmentioning
confidence: 81%
“…This suggests a functional dependence between AT2 and MasR for the AT2-induced generation of neurospheres. Accumulating evidence shows that both receptors are co-localized, form heterodimers, and have different functional interactions in different cells and experimental conditions [27,[95][96][97], and recent data from our laboratory (unpublished) showed that young AT2-KO mice show a reduced expression of MasR in the substantia nigra and striatum, which may also contribute to the decrease in proliferation and neurogenesis observed in the V-SVZ of AT2-KO mice. Therefore, although RAS receptors have been associated with different cellular and physiological responses, their role in neurogenesis is complex, as shown by the present results that reveal the presence of AT1, AT2, and MasR interactions possibly both in physiological or pathological situations.…”
Section: Discussionmentioning
confidence: 81%
“…We and others have demonstrated that the protective effects of Ang‐(1‐7) on atherosclerosis were largely blocked by A779 (Yang et al, ) or PD123319 (Tesanovic et al, ). Recently, AT 2 and Mas receptors were found to share 31% sequence identity (Villela et al, ), and these two receptors were colocalized and functionally interdependent in obese Zucker rat kidney (Patel, Ali, Samuel, Steckelings, & Hussain, ). More recently, Leonhardt et al elegantly demonstrated the formation of heterodimers of Mas and AT 2 receptors and thus inhibition of one of the heterodimer partners may cause inhibition of the other (Leonhardt et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable interest in the balance between ACE/Ang-II/AT1R axis and the ACE2/Ang-(1-7)/ MasR axis in blood pressure homeostasis and cardiovascular function (as shown in Figure-1). Interestingly, AT2R is normally induced by activation of the ACE2/Ang-(1-7)/MasR axis, while more recent evidence suggests that Ang-(1-7) may activate AT2R to antagonize AT1Rmediated effects [23,24].…”
Section: Distribution Of Pulmonary Ras Componentsmentioning
confidence: 99%